The Idiot : A Novel in Two Books (Book Two) - Dostoyevsky, Fyodor; Translated by Katzer, Julius (Moscow Progress Publishers, 1971)
Prince Myshkin, a good yet simple man, is out of place in the corrupt world created by Russia's ruling class.
Include Illustration
Keywords: Russia -- Social conditions -- Princes